Synthesis, Spectral Studies, and Theoretical Treatment of some New Metal Complexes with Tridentate Ligand (Schiff and Mannich Base) (Baghdad Science Journal, 2016)
New metal ions complexes of tridentate ligand (1-((dicyclohexylamino) methyl)-3-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrzol-4-ylimino) indolin-2-one) have been synthesized and characterized by chemical-physical analysis. The ligand acts as a tridentate for the complexation reaction with all metal ions. The new complexes, possessing the general formula [M(L)Cl]Cl where M=[Ni(II), Cu(II), Zn(II), Pd(II), Cd(II), Pt(IV) and Hg(II) ] ,show tetrahedral geometry. All complexes ,except Pd(II) complex which has a square planar geometry and Pt(IV) which show an octahedral geometry. The geometry of the prepared compounds has been proposed in another method theoretically by using one of the calculation molecular programs (Hyper chem.-6) program. Besides the comparison between the experimental results with the theoretical ones, show that the experimental results are so close to the theoretical counterpart.